Three-dimensional resistivity structure in the hydrothermal system beneath Ganzi Basin, eastern margin of Tibetan Plateau. (June 2021) - Cheng, Yuanzhi; Pang, Zhonghe; Di, Qingyun; Chen, Xiaobin; Kong, Yanlong
Highlights: Three-dimensional electrical resistivity structure beneath Ganzi Basin, eastern margin of Tibetan Plateau was obtained. 3D electrical model reveals the shallow and deep geothermal reservoirs in Ganzi geothermal system. The Ganzi fault provides the pathway for transport heat and the circulation of geothermal fluids. Abstract: The Ganzi geothermal system located in the eastern margin of Tibetan Plateau, is found to distribute the strongly active surface manifestations, such as boiling springs, and fumaroles. The resistivity structure of high-temperature hydrothermal system beneath Ganzi Basin has been obtained from the three-dimensional (3-D) magnetotelluric inversion of 103 broadband MT stations in period range from 320 Hz to 1000s. The MT stations have an average spacing of 500 m and completely cover the Ganzi Basin. The detailed 3-D resistivity structure which the authors found has been described characteristics of the shallow and deep geothermal reservoirs as well as to correlate with the structural features present in the Ganzi Basin. The shallow geothermal reservoir is mainly composed of the sedimentary layer, with a depth of 300−800 m, while the deep geothermal reservoir mainly consists of the fault fracture zone with a depth of 1−5 km. The porosity of the geothermal reservoirs is in the range 5–10 %, estimated based on the resistivity model. The Ganzi fault provides the pathway for transport heat and the circulation of geothermal fluids. The possible heat source for the Ganzi geothermal system has been attributed to tectonic deformation heating in the crust, radiogenic heat production derived from the decay of U, Th and K, and heat from the mantle.